Manganese dioxide nanofiber catalyst with hollow structure as well as preparation method and application of manganese dioxide nanofiber catalyst
By preparing hollow structure manganese dioxide nanofiber catalysts on carbon fiber templates, the problems of complex synthesis, poor stability and nanoparticle agglomeration of existing manganese oxide catalysts are solved, and efficient catalytic performance and new pollutant removal effect are achieved.
Patent Information
- Application Number
- CN202411650173.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-25
AI Technical Summary
The existing manganese oxide catalysts are complex in the synthesis process, have poor chemical stability and low catalytic efficiency, and nanoparticles are prone to agglomeration and difficult to recover.
Carbon fibers are used as templates, and hollow structure manganese dioxide nanofiber catalysts (MnO2@Mn-CNF) are prepared through electrospinning, preoxidation treatment and high-temperature pyrolysis to improve the utilization efficiency and stability of the catalyst.
The directional growth of MnO2 nanorods and the formation of hollow structures have been achieved, the problem of nanoparticle agglomeration has been solved, and the activation efficiency of peracetic acid and the efficient removal ability of new pollutants have been improved.
Smart Images

Figure CN119500110A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of pollutant catalysis, and in particular to a hollow structured manganese dioxide nanofiber catalyst and a preparation method and application thereof. Background Art
[0002] Emerging Contaminants (ECs) are a class of pollutants that exist in trace or trace amounts in the environment but pose a potential threat to organisms and the ecological environment. With the continuous updating and iteration of analytical detection methods and technologies, they have been widely detected in water environments and pose a potential hazard to the ecological environment. Advanced oxidation technology can produce a variety of reactive oxygen species with high oxidation potentials, such as hydroxyl radicals, which have significant advantages in the deep mineralization of emerging pollutants. Peracetic acid, as an oxidant with moderate oxidation potential and environmental friendliness, and advanced oxidation technology based on peracetic acid can produce a variety of reactive oxygen species including alkoxy radicals, is an important branch in the field of advanced oxidation. Among them, it is particularly noteworthy that in the field of heterogeneous catalysis, the removal of pollutants often relies more on the interfacial reaction between the oxidant and the pollutant on the catalyst surface. Therefore, constructing an efficient and stable microscopic reaction environment is the goal of preparing environmental catalytic materials, and it is also a challenge faced in achieving efficient utilization of reactive oxygen species.
[0003] Due to its high catalytic activity and low biotoxicity, manganese oxides are widely used in the study of heterogeneous advanced oxidation systems. However, manganese oxide catalysts still have disadvantages such as complex synthesis process, poor chemical stability and low catalytic efficiency. The electrostatic forces, van der Waals forces between nanoparticles and possible chemical bonds between some particles can also cause them to agglomerate, thereby reducing the catalytic efficiency and making it difficult to recover from the environment. One strategy to solve this problem is to fix the nanocatalyst on the carrier template through the carrier effect. Carbon materials are usually used as carriers to solve the agglomeration effect of the above-mentioned nanocatalysts because of their stable chemical properties. Among them, carbon fiber as a carrier has been widely used in the fields of environment, energy, and catalysis. Due to its large specific surface area and modifiability, it is an ideal carrier choice and provides sufficient conditions for constructing the microenvironment required for catalytic reactions.
[0004] Therefore, it is of great significance to construct manganese oxide catalysts using carbon fibers as templates to achieve controllable growth of nanocatalysts while improving the utilization efficiency of catalysts. Summary of the invention
[0005] The purpose of the present invention is to provide a hollow structure manganese dioxide nanofiber catalyst and its preparation method and application in order to overcome the deficiencies of the prior art, so as to achieve the purpose of improving the activation efficiency of peracetic acid and efficiently removing new pollutants.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing a hollow structure manganese dioxide nanofiber catalyst, comprising the following steps:
[0008] 1) mixing manganese acetylacetonate, N,N-dimethylformamide and polyacrylonitrile to obtain a precursor solution;
[0009] 2) electrospinning the precursor solution and then drying it to obtain a metal-polymer nanofiber membrane;
[0010] 3) The metal-polymer nanofiber membrane is sequentially subjected to pre-oxidation treatment and high-temperature pyrolysis to obtain Mn / N-carbon nanofibers;
[0011] 4) Mn / N-carbon nanofibers and potassium permanganate are mixed and ground to obtain a mixture; the mixture, water and concentrated sulfuric acid are reacted to obtain a hollow structure manganese dioxide nanofiber catalyst.
[0012] Preferably, in step 1), the mass ratio of manganese acetylacetonate to polyacrylonitrile is 1.3-1.5:2; the mass volume ratio of manganese acetylacetonate to N,N-dimethylformamide is 1.3-1.5 g:20 mL; the mixing time is 10-14 h, and the mixing is carried out under stirring conditions at a stirring speed of 800-1200 rpm.
[0013] Preferably, the voltage of the electrospinning in step 2) is 13-17 kV, the propulsion speed of the precursor solution during the electrospinning process is 0.8-1.2 mL / h, the receiving distance is 13-17 cm, and the relative humidity is ≤50%;
[0014] The drying temperature is 55-65° C., and the drying time is 10-14 hours.
[0015] Preferably, the temperature of the pre-oxidation treatment in step 3) is 180-220° C., the time of the pre-oxidation treatment is 1.7-2.5 h, and the heating rate to the pre-oxidation treatment temperature is 8-12° C. / min.
[0016] Preferably, the temperature of the high-temperature pyrolysis in step 3) is 770-830°C, the time of the high-temperature pyrolysis is 1.7-2.5h, the heating rate to the high-temperature pyrolysis temperature is 4-6°C / min, and the high-temperature pyrolysis is carried out under a nitrogen atmosphere.
[0017] Preferably, in step 4), the mass ratio of the Mn / N-carbon nanofibers to potassium permanganate is 1:4-8, and the mass volume ratio of the Mn / N-carbon nanofibers, water and concentrated sulfuric acid is 0.2 g:75-85 mL:3-5 mL.
[0018] Preferably, the grinding time in step 4) is 18 to 22 minutes, the mass concentration of the concentrated sulfuric acid is 97 to 99%, the reaction temperature is 75 to 85° C., and the reaction time is 3.5 to 4.5 hours.
[0019] Preferably, after the reaction in step 4) is completed, a suspension is obtained, and the suspension is washed and dried in sequence to obtain a hollow structure manganese dioxide nanofiber catalyst; the washing reagent is water, the drying temperature is 47-53° C., and the drying time is 10-14 hours.
[0020] The invention also provides a hollow structure manganese dioxide nanofiber catalyst prepared by the preparation method.
[0021] The invention also provides the use of the hollow structure manganese dioxide nanofiber catalyst in activating peracetic acid to degrade new pollutants.
[0022] The beneficial effects of the present invention include the following:
[0023] 1) The Mn / N-carbon nanofiber template used in the present invention has the characteristics of uniform structure and uniform element distribution, which is conducive to further chemical modification and provides a good carrier environment for the subsequent directional generation of MnO2.
[0024] 2) The MnO2@Mn-CNF catalyst prepared by the present invention has a distinct hollow structure, and the generated MnO2 nanorods are in a state of directional growth along the properties of carbon fibers, which solves the defect that manganese dioxide nanoparticles are easy to agglomerate.
[0025] 3) The MnO2@Mn-CNF catalyst prepared by the present invention makes maximum use of the effective active sites of the MnO2 nanorods. At the same time, the nanoconfinement effect formed by the hollow structure is beneficial to the subsequent activation of peracetic acid and the rapid degradation of pollutants. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 X-ray diffraction patterns of the MnO2@Mn-CNF catalysts of Examples 1 to 3, the Mn-CNF of Example 1, and the MnO2 powder of Comparative Example 1;
[0027] Figure 2 Scanning electron microscope images of the MnO2@Mn-CNF catalyst of Example 1 and the MnO2 powder of Comparative Example 1, wherein a and b are MnO2 powders, and c and d are MnO2@Mn-CNF catalysts;
[0028] Figure 3 The transmission electron microscope image and element distribution map of the MnO2@Mn-CNF catalyst of Example 1;
[0029] Figure 4 Electrochemical impedance diagrams of the MnO2@Mn-CNF catalyst of Example 1 and the MnO2 powder of Comparative Example 1;
[0030] Figure 5 The cyclic voltammetry curves of the MnO2@Mn-CNF catalyst of Example 1 and the MnO2 powder of Comparative Example 1;
[0031] Figure 6 The effect of the MnO2@Mn-CNF catalysts of Examples 1 to 3 and the MnO2 powder of Comparative Example 1 in activating peracetic acid to degrade bisphenol A;
[0032] Figure 7 It chronoamperometric signal curves of the MnO2@Mn-CNF catalyst of Example 1 and the MnO2 powder of Comparative Example 1. DETAILED DESCRIPTION
[0033] The present invention provides a method for preparing a hollow structure manganese dioxide nanofiber catalyst, comprising the following steps:
[0034] 1) mixing manganese acetylacetonate, N,N-dimethylformamide and polyacrylonitrile to obtain a precursor solution;
[0035] 2) electrospinning the precursor solution and then drying it to obtain a metal-polymer nanofiber membrane;
[0036] 3) The metal-polymer nanofiber membrane is sequentially subjected to pre-oxidation treatment and high-temperature pyrolysis to obtain Mn / N-carbon nanofibers;
[0037] 4) Mn / N-carbon nanofibers and potassium permanganate are mixed and ground to obtain a mixture; the mixture, water and concentrated sulfuric acid are reacted to obtain a hollow structure manganese dioxide nanofiber catalyst.
[0038] In the present invention, the manganese acetylacetonate (C 15 H 21 The mass ratio of manganese acetylacetonate to N,N-dimethylformamide is preferably 1.3-1.5 g:20 mL, more preferably 1.35-1.45 g:20 mL, and more preferably 1.4-1.41 g:20 mL; the mixing time is preferably 10-14 h, more preferably 11-13 h, and more preferably 12 h. The mixing is carried out under stirring conditions, and the stirring speed is preferably 800-1200 rpm, more preferably 900-1100 rpm, and more preferably 1000 rpm.
[0039] In the present invention, the molecular weight of polyacrylonitrile is preferably 149,000 to 151,000, more preferably 150,000.
[0040] In the present invention, the mixing in step 1) is preferably that manganese acetylacetonate is dissolved in N,N-dimethylformamide, and polyacrylonitrile is slowly added after complete dissolution; if the polyacrylonitrile is added too quickly, it is easy to form "lumps" in N,N-dimethylformamide, so it needs to be added slowly like an "hourglass", the purpose is to prevent the viscosity of some parts in the system from being too high, to ensure that the polyacrylonitrile is completely dissolved, and to form a uniformly mixed precursor solution.
[0041] In the present invention, the voltage of the electrospinning in step 2) is preferably 13-17 kV, more preferably 14-16 kV, and more preferably 15 kV. During the electrospinning process, the propulsion speed of the precursor solution is preferably 0.8-1.2 mL / h, more preferably 0.9-1.1 mL / h, and more preferably 1 mL / h; the receiving distance is preferably 13-17 cm, more preferably 14-16 cm, and more preferably 15 cm; the relative humidity is preferably ≤50%, more preferably ≤45%, and more preferably ≤40%;
[0042] The drying temperature is preferably 55 to 65° C., more preferably 58 to 62° C., more preferably 60° C., and the drying time is preferably 10 to 14 h, more preferably 11 to 13 h, more preferably 12 h.
[0043] In the present invention, the needle used for spinning has a specification of 24G, and the metal-polymer nanofibers are collected with aluminum foil.
[0044] In the present invention, the temperature of the pre-oxidation treatment in step 3) is preferably 180-220°C, more preferably 190-210°C, and more preferably 200°C. The time of the pre-oxidation treatment is preferably 1.7-2.5h, and more preferably 2-2.2h. The heating rate to the pre-oxidation treatment temperature is preferably 8-12°C / min, and more preferably 9-11°C / min, and more preferably 10°C / min.
[0045] In the present invention, the temperature of the high-temperature pyrolysis in step 3) is preferably 770-830°C, more preferably 780-820°C, and more preferably 800°C; the time of the high-temperature pyrolysis is preferably 1.7-2.5h, more preferably 2-2.2h, and the heating rate to the high-temperature pyrolysis temperature is preferably 4-6°C / min, more preferably 4.5-5.5°C / min, and more preferably 5°C / min. The high-temperature pyrolysis is preferably carried out under a nitrogen atmosphere.
[0046] In the present invention, the mass ratio of the Mn / N-carbon nanofibers (Mn-CNF) and potassium permanganate in step 4) is preferably 1:4-8, and more preferably 1:6-8; the mass volume ratio of the Mn / N-carbon nanofibers, water and concentrated sulfuric acid is preferably 0.2 g:75-85 mL:3-5 mL, and more preferably 0.2 g:77-82 mL:3.5-4.5 mL, and more preferably 0.2 g:79-80 mL:4 mL.
[0047] In the present invention, the mass ratio of Mn / N-carbon nanofibers and potassium permanganate can control the morphology of the directional growth of MnO2 on the fiber surface.
[0048] In the present invention, the grinding time in step 4) is preferably 18 to 22 minutes, more preferably 19 to 21 minutes, and more preferably 20 minutes; the mass concentration of the concentrated sulfuric acid is preferably 97 to 99%, and more preferably 98%; the reaction temperature is preferably 75 to 85°C, and more preferably 78 to 82°C, and more preferably 80°C; the reaction time is preferably 3.5 to 4.5 hours, and more preferably 3.7 to 4.2 hours, and more preferably 4 hours.
[0049] In the present invention, concentrated sulfuric acid can enhance the oxidizing ability of potassium permanganate.
[0050] In the present invention, after the reaction in step 4) is completed, a suspension is obtained, and the suspension is washed and dried in sequence to obtain a hollow structure manganese dioxide nanofiber catalyst; the washing reagent is preferably water, the drying temperature is preferably 47 to 53°C, more preferably 48 to 52°C, more preferably 50°C, and the drying time is preferably 10 to 14h, more preferably 11 to 13h, more preferably 12h.
[0051] The chemical reagents in the present invention are all of analytical grade and can be used directly without further purification.
[0052] The present invention also provides a hollow structure manganese dioxide nanofiber catalyst (MnO2@Mn-CNF) prepared by the preparation method.
[0053] The invention also provides the use of the hollow structure manganese dioxide nanofiber catalyst in activating peracetic acid (PAA) to degrade new pollutants.
[0054] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0055] Example 1
[0056] Dissolve 1.41g of manganese acetylacetonate in 20mL of N,N-dimethylformamide. After complete dissolution, slowly add 2g of polyacrylonitrile (molecular weight 150000) and stir at 1000rpm for 12h at room temperature to form a uniformly mixed precursor solution. Transfer 8mL of the precursor solution into a 10mL syringe with a 24G needle. Spin at a voltage of 15kV, a propulsion speed of 1mL / h, a receiving distance of 15cm, and a relative humidity of 45%. Collect the metal-polymer nanofibers with aluminum foil and dry them in a blast drying oven at 60°C for 12h to obtain a metal-polymer nanofiber membrane.
[0057] The metal-polymer nanofiber membrane was pre-oxidized in a muffle furnace, heated to 200°C at a heating rate of 10°C / min, and pre-oxidized at 200°C for 2h. Subsequently, it was heated to 800°C at a heating rate of 5°C / min in a tubular furnace under a nitrogen atmosphere, and maintained at 800°C for 2h for high-temperature pyrolysis to obtain Mn / N-carbon nanofibers, recorded as Mn-CNF.
[0058] 0.2g Mn-CNF and 1.6g potassium permanganate were fully ground in an agate mortar for 20min, and the evenly ground mixture was poured into 80mL ultrapure water, and then 4mL of concentrated sulfuric acid with a mass concentration of 98% was added. Then, it was transferred to a water bath and reacted at 80℃ for 4h. After the reaction, the suspension was filtered and washed several times with deionized water until the filtrate was transparent and colorless, and the pH value of the supernatant was greater than 5. Finally, the washed sample was dried in a blast drying oven at 50℃ for 12h to obtain a hollow structure manganese dioxide nanofiber catalyst, which was recorded as MnO2@Mn-CNF (1:8).
[0059] Example 2
[0060] The mass of potassium permanganate in Example 1 was changed to 1.2 g, and the other conditions were the same as in Example 1 to obtain MnO2@Mn-CNF (1:6).
[0061] Example 3
[0062] The mass of potassium permanganate in Example 1 was changed to 0.8 g, and the other conditions were the same as in Example 1 to obtain MnO2@Mn-CNF (1:4).
[0063] Example 4
[0064] Dissolve 1.3g of manganese acetylacetonate in 20mL of N,N-dimethylformamide. After complete dissolution, slowly add 2g of polyacrylonitrile (molecular weight 149000) and stir at 900rpm for 13h at room temperature to form a uniformly mixed precursor solution. Transfer 8mL of the precursor solution into a 10mL syringe with a 24G needle. Spin at a voltage of 14kV, a propulsion speed of 0.9mL / h, a receiving distance of 14cm, and a relative humidity of 40%. Collect the metal-polymer nanofibers with aluminum foil and dry them in a blast drying oven at 58°C for 13h to obtain a metal-polymer nanofiber membrane.
[0065] The metal-polymer nanofiber membrane was pre-oxidized in a muffle furnace, heated to 190°C at a heating rate of 9°C / min, and pre-oxidized at 190°C for 2.5h. Subsequently, in a tubular furnace under a nitrogen atmosphere, the temperature was increased to 780°C at a heating rate of 4.5°C / min, and maintained at 780°C for 2.5h for high-temperature pyrolysis to obtain Mn / N-carbon nanofibers, recorded as Mn-CNF.
[0066] 0.2g Mn-CNF and 1.4g potassium permanganate were fully ground in an agate mortar for 20min, and the evenly ground mixture was poured into 85mL ultrapure water, and then 4.5mL of concentrated sulfuric acid with a mass concentration of 98% was added. Then, it was transferred to a water bath and reacted at 78°C for 4.2h. After the reaction, the suspension was filtered and washed several times with deionized water until the filtrate was transparent and colorless, and the pH value of the supernatant was greater than 5. Finally, the washed sample was dried in a blast drying oven at 48°C for 13h to obtain a hollow structure manganese dioxide nanofiber catalyst.
[0067] Example 5
[0068] Dissolve 1.5g of manganese acetylacetonate in 20mL of N,N-dimethylformamide. After complete dissolution, slowly add 2g of polyacrylonitrile (molecular weight 151000) and stir at 1100rpm for 11h at room temperature to form a uniformly mixed precursor solution. Transfer 8mL of the precursor solution into a 10mL syringe with a 24G needle. Spin at a voltage of 16kV, a propulsion speed of 1.1mL / h, a receiving distance of 16cm, and a relative humidity of 45%. Collect the metal-polymer nanofibers with aluminum foil and dry them in a blast drying oven at 62°C for 11h to obtain a metal-polymer nanofiber membrane.
[0069] The metal-polymer nanofiber membrane was pre-oxidized in a muffle furnace, heated to 210°C at a heating rate of 11°C / min, and pre-oxidized at 210°C for 2h. Subsequently, in a tubular furnace under a nitrogen atmosphere, the temperature was increased to 820°C at a heating rate of 5.5°C / min, and maintained at 820°C for 2h for high-temperature pyrolysis to obtain Mn / N-carbon nanofibers, recorded as Mn-CNF.
[0070] 0.2g Mn-CNF and 1.0g potassium permanganate were fully ground in an agate mortar for 20min, and the evenly ground mixture was poured into 77mL ultrapure water, and then 3.5mL of concentrated sulfuric acid with a mass concentration of 98% was added. Then, it was transferred to a water bath and reacted at 82°C for 3.7h. After the reaction, the suspension was filtered and washed several times with deionized water until the filtrate was transparent and colorless, and the pH value of the supernatant was greater than 5. Finally, the washed sample was dried in a blast drying oven at 52°C for 11h to obtain a hollow structure manganese dioxide nanofiber catalyst.
[0071] Comparative Example 1
[0072] After grinding 2.45g of tetrahydrated manganese acetate and 1.58g of KMnO4 in an agate mortar for 20 minutes, the uniformly ground mixture was added to 80mL of deionized water, and then 4mL of 98% sulfuric acid was added, and then transferred to a water bath and reacted at 80°C for 4h. After the reaction, the suspension was washed several times with deionized water. Finally, the washed sample was dried in a blast drying oven at 50°C for 12h to obtain brown-black MnO2 powder.
[0073] The X-ray diffraction patterns of the MnO2@Mn-CNF catalysts of Examples 1 to 3, the Mn-CNF of Example 1 and the MnO2 powder of Comparative Example 1 are as follows: Figure 1 As shown. Figure 1 It can be seen that the crystal form of the MnO2 powder of Comparative Example 1 and the MnO2@Mn-CNF catalysts of Examples 1 to 3 is mainly α-MnO2.
[0074] The scanning electron microscope images of the MnO2@Mn-CNF catalyst of Example 1 and the MnO2 powder of Comparative Example 1 are as follows: Figure 2 As shown in the figure, a and b are MnO2 powders, c and d are MnO2@Mn-CNF catalysts. It can be seen from the figure that when there is no fiber carrier, the MnO2 nanorods generated by the hydrothermal method in Comparative Example 1 will eventually agglomerate into micron-sized particles. The MnO2 nanorods prepared by the present invention can grow in a directional manner along the carbon fiber template and eventually form hollow MnO2 nanofibers.
[0075] The transmission electron microscopy image and element distribution diagram of the MnO2@Mn-CNF catalyst of Example 1 are shown in Figure 3 As shown in the figure, it can be seen that the colors of Mn and O elements are darker along the edge of the fiber, while the colors in the middle are lighter, which further illustrates that the MnO2@Mn-CNF catalyst has a hollow structure.
[0076] Application Example 1
[0077] The MnO2@Mn-CNF catalyst of Example 1 and the MnO2 powder of Comparative Example 1 were loaded onto glassy carbon electrodes for electrocatalytic performance testing. The specific operation was as follows: 10 mg of the catalyst of Example 1 and the MnO2 powder of Comparative Example 1 were added to 950 μL of ethanol solution (250 μL of anhydrous ethanol and 700 μL of water), and then 50 μL of Nafion solution was added, and ultrasonicated at a frequency of 100 kHz for 15 minutes. 100 μL of the obtained sample was added dropwise to a clean ITO electrode and dried at room temperature as a working electrode; the platinum electrode was used as the counter electrode, and the reference electrode was an Ag / AgCl electrode.
[0078] Cyclic voltammetry (CV) test: the electrolyte was 0.5 mol / L sodium sulfate aqueous solution, the voltage window was -1 to 1 V, and the scan rate was 20 mV / s.
[0079] Electrochemical impedance spectroscopy (EIS) test: The test frequency range is 0.1 to 100 kHz, and the AC amplitude is 10 mV.
[0080] The electrochemical impedance spectroscopy of the MnO2@Mn-CNF catalyst of Example 1 and the MnO2 powder of Comparative Example 1 is shown in Figure 4 As shown in the figure, it can be seen that the radius of the MnO2@Mn-CNF catalyst in the high-frequency region is significantly smaller than that of the MnO2 powder, while the slope of the MnO2@Mn-CNF catalyst in the low-frequency region is significantly higher than that of the MnO2 powder, indicating that the charge transfer rate of the MnO2@Mn-CNF catalyst is significantly better than that of the MnO2 powder. The cyclic voltammetry curves of the MnO2@Mn-CNF catalyst of Example 1 and the MnO2 powder of Comparative Example 1 are shown in Figure 5 As shown. Figure 5 It can be seen that the MnO2@Mn-CNF catalyst has a higher specific capacitance than MnO2 powder, and thus has greater catalytic potential.
[0081] Application Example 2
[0082] The oxidant is environmentally friendly peracetic acid (PAA), and the model pollutant is a typical new pollutant bisphenol A (BPA). The catalysts are the MnO2@Mn-CNF catalysts of Examples 1 to 3 and the MnO2 powder of Comparative Example 1. 10 mg of the catalyst and the powder are respectively put into 100 mL of BPA simulated wastewater (the concentration of BPA is 50 μmol / L). After uniform dispersion, PAA is added to start the reaction. The initial concentration of PAA in the system is 200 μmol / L. The concentration change of BPA is detected within a certain period of time.
[0083] In order to intuitively demonstrate the interfacial action mechanism and electron transfer process between the oxidant and the pollutant on the catalyst surface, the it chronoamperometry was used to monitor the current changes in the catalytic process. The specific operation was as follows: the test was started when the initial voltage was 0, and PAA was first added to the Na2SO4 electrolyte at 200s, and the concentration of PAA in the electrolyte was controlled to be 1mmol / L, and the current changes were recorded. Then, the pollutant BPA was added at 400s, and the concentration of the pollutant in the electrolyte was controlled to be 10mg / L, and the current changes were recorded until 600s.
[0084] The effects of the MnO2@Mn-CNF catalysts of Examples 1 to 3 and the MnO2 powder of Comparative Example 1 in activating peracetic acid to degrade bisphenol A are shown in FIG. Figure 6 As shown. Figure 6 It can be seen that compared with MnO2 powder, the activation performance of MnO2@Mn-CNF catalyst for PAA is further improved, and BPA can be completely removed within 60 minutes.
[0085] The it chronoamperometric signal curves of the MnO2@Mn-CNF catalyst of Example 1 and the MnO2 powder of Comparative Example 1 are as follows: Figure 7 As shown. Figure 7 It can be seen that after adding PAA, an obvious negative current signal appeared, indicating that the electron transfer process first occurred between the catalyst and the oxidant. Subsequently, BPA was added, and an obvious negative current signal appeared again in the MnO2@Mn-CNF catalyst system, indicating that BPA, as an electron donor, transferred electrons to PAA, and this process corresponds to the oxidative degradation of BPA. The current signal of the MnO2@Mn-CNF system is significantly stronger than that of the MnO2 system. The test results of the it curve are consistent with the results of BPA degradation, proving that the MnO2@Mn-CNF catalyst has excellent activation performance for PAA and has a high efficiency degradation effect on BPA.
[0086] The present invention uses Mn-N doped carbon fiber as a template and then performs potassium permanganate corrosion oxidation under hydrothermal conditions to finally form a MnO2 nanofiber catalyst (MnO2@Mn-CNF) with a hollow structure. The MnO2@Mn-CNF catalyst prepared by the present invention has the characteristics of controllable structure and directional growth of MnO2 nanorods into a hollow structure, and can be applied to the field of environmental catalysis, especially heterogeneous advanced oxidation processes.
[0087] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a hollow structured manganese dioxide nanofiber catalyst, characterized in that: The following steps are included: 1) mixing manganese acetylacetonate, N,N-dimethylformamide and polyacrylonitrile to obtain a precursor solution; 2) electrospinning the precursor solution and then drying it to obtain a metal-polymer nanofiber membrane; 3) The metal-polymer nanofiber membrane is sequentially subjected to pre-oxidation treatment and high-temperature pyrolysis to obtain Mn / N-carbon nanofibers; 4) Mn / N-carbon nanofibers and potassium permanganate are mixed and ground to obtain a mixture; the mixture, water and concentrated sulfuric acid are reacted to obtain a hollow structure manganese dioxide nanofiber catalyst.
2. The preparation method according to claim 1, characterized in that: Step 1) The mass ratio of manganese acetylacetonate to polyacrylonitrile is 1.3-1.5:2; the mass volume ratio of manganese acetylacetonate to N,N-dimethylformamide is 1.3-1.5 g:20 mL; the mixing time is 10-14 h, and the mixing is carried out under stirring conditions at a stirring speed of 800-1200 rpm.
3. The preparation method according to claim 1 or 2, characterized in that: Step 2) The voltage of the electrospinning is 13-17 kV. During the electrospinning process, the propulsion speed of the precursor solution is 0.8-1.2 mL / h, the receiving distance is 13-17 cm, and the relative humidity is ≤50%; The drying temperature is 55-65° C., and the drying time is 10-14 hours.
4. The preparation method according to claim 3, characterized in that: Step 3) The pre-oxidation temperature is 180-220° C., the pre-oxidation time is 1.7-2.5 hours, and the heating rate to the pre-oxidation temperature is 8-12° C. / min.
5. The preparation method according to claim 4, characterized in that: Step 3) The high temperature pyrolysis temperature is 770-830° C., the high temperature pyrolysis time is 1.7-2.5 hours, the heating rate to the high temperature pyrolysis temperature is 4-6° C. / min, and the high temperature pyrolysis is carried out under a nitrogen atmosphere.
6. The preparation method according to claim 4 or 5, characterized in that: Step 4) The mass ratio of the Mn / N-carbon nanofibers to potassium permanganate is 1:4-8, and the mass volume ratio of the Mn / N-carbon nanofibers, water and concentrated sulfuric acid is 0.2 g:75-85 mL:3-5 mL.
7. The preparation method according to claim 6, characterized in that: Step 4) The grinding time is 18 to 22 minutes, the mass concentration of the concentrated sulfuric acid is 97 to 99%, the reaction temperature is 75 to 85° C., and the reaction time is 3.5 to 4.5 hours.
8. The preparation method according to claim 7, characterized in that: Step 4) After the reaction is completed, a suspension is obtained, and the suspension is washed and dried in sequence to obtain a hollow structure manganese dioxide nanofiber catalyst; the washing reagent is water, the drying temperature is 47-53° C., and the drying time is 10-14 hours.
9. The hollow structure manganese dioxide nanofiber catalyst prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the hollow structure manganese dioxide nanofiber catalyst according to claim 9 in activating peracetic acid to degrade new pollutants.